2023
DOI: 10.3390/ijerph20105884
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity in Higher Education: A Contemporary Review of Impacts and Explorations of Solutions

Abstract: Food insecurity is a global phenomenon which impacts a variety of social, economic, and life-stage groups. One such group affected by food insecurity is college students, who tend to experience food insecurity at a prevalence which exceeds the average of their local communities. The impacts of food insecurity in this population are multifaceted and have implications for their college experience and beyond. Food insecurity has been observed to have negative effects on college student academic performance, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 121 publications
0
9
1
Order By: Relevance
“…Food insecurity also affects society as a whole, impacting the future workforce and the availability of qualified talent. Therefore, addressing food insecurity among college students should be a priority for college administrators to meet the needs of their students, maintain their reputations, and meet missions of excellence (Loofbourrow and Scherr, 2023 ).…”
Section: Impact Of University Participation In Ensuring Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity also affects society as a whole, impacting the future workforce and the availability of qualified talent. Therefore, addressing food insecurity among college students should be a priority for college administrators to meet the needs of their students, maintain their reputations, and meet missions of excellence (Loofbourrow and Scherr, 2023 ).…”
Section: Impact Of University Participation In Ensuring Food Securitymentioning
confidence: 99%
“…University participation in ensuring food security could also impact the economy. Research from Australian universities indicates a high prevalence of food insecurity among college students, ranging from 38% to 48% (Loofbourrow and Scherr, 2023 ). This can affect students’ finances, academic performance, and physical and mental health, ultimately influencing their future economic contributions.…”
Section: Impact Of University Participation In Ensuring Food Securitymentioning
confidence: 99%
“…Food insecurity is a major issue that has been linked to a myriad of physical and mental health conditions among university students [ 13 ]. Numerous studies have reported that students facing food insecurity had higher odds of reporting unhealthy diets, altered sleep quality, stress, anxiety, depression, and poor academic performance relative to their food-secure counterparts [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity often goes undetected among college students, particularly amidst the demands of academia and the transition to independent living. Studies reveal that, on average, approximately 30% of college students experience FI during their academic careers, a rate more than double the national average [1][2][3][4][5][6][7]. Further research across diverse institutions identifies additional groups at greater risk of FI, including those living in urban communities, students of color, Pell Grant recipients, athletes without meal plans, first-generation students, and those with pre-existing FI [8,9].…”
Section: Introductionmentioning
confidence: 99%